Hubungan Postur Kerja Tidak Alamiah dengan Keluhan MSDs pada Pekerja PT. Batang Alum Industrie - Teguh Irawan; Jaya Maulana; Siti Maesaroh (LPPM Universitas Pekalongan, 2023)
Unnatural work postures or awkward work postures are work postures in which the body moves away from its natural position, such as a back that is too bent, hands in a raised position, squatting, body twisting, and so on. Complaints on the musculoskeletal system are complaints on parts of the skeletal muscles that are felt by a person. If the muscles receive static loads repeatedly and for a long time, it can cause complaints in the form of damage to joints, ligaments and tendons. Whereas in Indonesia, based on the results of basic health research (Riskesdas, 2013), the prevalence of joint disease based on the results of diagnoses by health workers in Indonesia is 11.9% and based on diagnoses or symptoms, 24.7%.This study aims to determine the relationship between work posture and complaints of musculoskeletal disorders (MSDs) in workers in the cyclamate production department at PT. Batang Alum Industrie with correlation description research design, cross sectional approach, a sample of 74 employees and total sampling technique. The results of the rank spearman test analysis found a significant relationship between work posture and complaints of musculoskeletal disorders (MSDs) in workers in the cyclamate production department at PT. Batang Alum Industrie results in a sig value of 0.000 (ƿ > 0.05) and a correlation coefficient of 0.409.Companies should provide training or guidance regarding good work posture according to ergonomics to workers so that workers apply and know good and correct work postures so that workers are comfortable at work. Workers should stretch their muscles to take advantage of their rest hours by doing muscle relaxation movements for about 5-10 minutes to improve blood circulation throughout the body.